11 The association of frailty and coronary artery plaque composition in high-risk older patients with non-st elevation acute coronary syndrome. (27th November 2017) - Gu, Sophie Zhaotao; Sinclair, Hannah; Latimer, James; Batty, Jonathan; Bagnall, Alan; Purcell, Ian; Das, Rajiv; Spyridopoulos, Ioakim; Edwards, Richard; Zaman, Azfar; Egred, Mohaned; Ahmed, Javed; et al.
Abstract : Introduction: The association of frailty with vulnerable plaques and plaque composition in older patients following non-ST elevation acute coronary syndrome (NSTEACS) is not known. Methods: 27 patients>70 years of age, admitted for invasive management of NSTEACS enrolled in the prospective observational ICON1 study, had Optical Coherence Tomography (OCT, St. Jude, Minneapolis, MN, USA) performed in all 3 coronary arteries. Frailty was assessed using the Fried criteria (score 0=robust, 1 or 2=pre frail and ≥3 is frail). OCT analyses were performed by QIvus 3.0 (Medis medical imaging systems, Leiden) at Newcastle University Angiography/IVUS/OCT Core Laboratory.% plaque composition (number of component [lipid, calcium, etc., ] frames/number of lesion frames×100) and presence of thin cap fibroatheroma (TCFA) and other OCT parameters are reported. The ICON1 study protocol is previously published. Results: There were 8 (29.6%) robust, 14 (51.9%) pre-frail, and 5 (18.5%) frail patients. Mean age was 80.2±3.9 years, and 16 (59.3%) patients were male. Total length imaged was 75.3±31.1 mm and total OCT frames analysed were 348±155/patient. TCFA was present in the culprit artery in 9 (33%) patients and 6 (22.2%) patients had a non-culprit artery TCFA; thus, overall 11 (40.7%) had at least one TCFA in their coronary arteries. There is no significant difference in plaque composition between frailty groups (table 1). Conclusions: In this selected high risk older patients presenting with NSTEACS, there was no difference in the coronary artery plaque composition or presence of high risk plaque among the frailty groups as evaluated using OCT.